2012
DOI: 10.1093/her/cys052
|View full text |Cite
|
Sign up to set email alerts
|

The social ecology of maternal infant care in socially and economically marginalized community in southern Israel

Abstract: This study aims to better understand the social ecology of infant care (IC) as experienced and perceived by mothers living in a deprived Arab Bedouin community in Israel, where children's health indicators are poor. We used the integrative model of García Coll et al. (García Coll C, Lamberty G, Jenkins R et al. An integrative model for the study of developmental competencies in minority children. Child Dev 1996; 67: 1891-914) and constructs of the Health Beliefs Model as a study framework for conducting focus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…This underestimation could also stem from other factors. While our sample is representative of all women in Israel of childbearing age, as most women in Israel visit the MCH clinics for immunizations and follow-up for their children, the poorest sector of Israeli society is still not included, as this demographic does not visit MCH clinics on a regular basis (Daoud, O’Campo, Anderson, Agbaria, & Shoham-Vardi, 2012; Daoud & Shoham-Vardi, 2015). This means their possible experiences of IPV were left out of the study.…”
Section: Discussionmentioning
confidence: 99%
“…This underestimation could also stem from other factors. While our sample is representative of all women in Israel of childbearing age, as most women in Israel visit the MCH clinics for immunizations and follow-up for their children, the poorest sector of Israeli society is still not included, as this demographic does not visit MCH clinics on a regular basis (Daoud, O’Campo, Anderson, Agbaria, & Shoham-Vardi, 2012; Daoud & Shoham-Vardi, 2015). This means their possible experiences of IPV were left out of the study.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with this notion we argue that the perspective of parents can add to our understanding of the complexity and interrelations of different contextual factors. Previous studies utilizing the integrative model by García Coll et al (1996) to study child development in the context of the Arab-Bedouins in Israel (e.g., Daoud, O’Campo, Anderson, Agbaria, & Shoham-Vardi, 2012; Daoud & Shoham-Vardi, 2015) found that infant care practices in the Bedouin population are strongly shaped by socioecological factors. For example, upon studying Bedouin mothers’ perceptions of infant care, Daoud et al (2012) conclude that the interaction of distal factors such as land disputes and the transition to an urbanized lifestyle, with proximal factors such as poor living conditions, poverty, and inadequate health care, challange infant care.…”
Section: An Ecological Context-informed Perspective On Riskmentioning
confidence: 99%
“…Despite extensive need, only one-third of the UVs have pre-schools and elementary schools (Fargeon and Rotem, 2016). Regarding the children's state of health, the statistics indicate a high occurrence of health problems, hospitalisation and domestic accidents compared to other populations, as well as low birth weights (Daoud et al, 2012). These data reflect daily life in the UVs and indicate the multiple risk factors that affect the welfare and security of Bedouin children at a young age, including fires, unsupervised traffic, open sewage pits, toxic gases that children inhale following garbage burning, stray dogs, etc.…”
Section: The Study Contextmentioning
confidence: 97%
“…Bedouin mothers are typically the main caretakers of children during early infancy. Regarding the children's state of health, the statistics indicate a high occurrence of health problems, hospitalisation and domestic accidents compared to other populations, as well as low birth weights (Daoud et al, 2012). Despite extensive need, only one-third of the UVs have pre-schools and elementary schools (Fargeon and Rotem, 2016).…”
Section: The Study Contextmentioning
confidence: 99%